1975
DOI: 10.1104/pp.56.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Studies of Cell Wall Enzymes and Growth

Abstract: If cell wall hydrolytic enzymes are involv-ed in extension growth, a correlation may be expected between hydrolytic activity of the cell walls and growth rate of the tissue from which the walls are prepared. Epicotyl sections from 0 to 5 mm, 6 to 10 mm, and 11 to 13 mm below the apical hook of pea seedlings (Pisum sativum var. Alaska) have relative growth rates of 100:15:2, respectivelv. The relative fl-glucosidase activities (units/mg wall) Data from several laboratories suggest that glycosidases play a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…It was also involved in autolysis in Cicer arietinum (Dopico et al 1989a). Correlation between g-glucosidase and rate of cell elongation has been reported by Murray and Bandursky (1975). Bucheli et al (1985), working with cotton fibres, related glucanases to growth while Tanimoto (1985) related growth to ot-galactosidase and a-arabinosidase in Pisum sativum.…”
Section: Resultsmentioning
confidence: 94%
“…It was also involved in autolysis in Cicer arietinum (Dopico et al 1989a). Correlation between g-glucosidase and rate of cell elongation has been reported by Murray and Bandursky (1975). Bucheli et al (1985), working with cotton fibres, related glucanases to growth while Tanimoto (1985) related growth to ot-galactosidase and a-arabinosidase in Pisum sativum.…”
Section: Resultsmentioning
confidence: 94%
“…Masuda et al (1985) reported that ␤-galactosidase activity was high in the growing cells and that the activity was related to polysaccharides such as galactan, arabinogalactan, and xyloglucan, which undergo changes during growth. Correlation between ␤-glucosidase and the rate of cell elongation has been reported by Murray and Bandurski (1975); Bucheli et al (1985), working with cotton fibers, related glucanases to growth, and Tanimoto (1985) related growth to ␣-galactosidase and ␣-arabinosidase in Pisum sativum. Thus, the conclusion that these glycosidases are related to the elongation growth (cell wall loosening) and structure of the cell wall has been drawn by several authors.…”
Section: Resultsmentioning
confidence: 99%
“…1). The maximal growth response at pH 5 in these segments is one which appeals to us in that many cell wall hydrolases show maximal enzyme activity at around pH 5 (15,16,18,19). Thus, increase in acidification rates elicited by GA3, resulting in attainment of pH values approximating 5 (compared with pH 5.6 in control segments) could be of major significance in GA3-stimulated growth, especially since GA3 starts to increase cell wall plasticity in the internode base within 60 min (3).…”
Section: Discussionmentioning
confidence: 95%